Dietary specialization mirrors Rapoport's rule in European geometrid moths. Issue 6 (1st April 2022) - Seifert, Carlo L.; Strutzenberger, Patrick; Hausmann, Axel; Fiedler, Konrad
Abstract: Aim: Latitudinal clines in dietary specialization and range size are used to explain biodiversity distributions at large spatial scales, such as the latitudinal diversity gradient. The aim of this study was to test whether dietary breadth (as a dimension of niche breadth) and range size decrease towards lower latitudes in a species‐rich clade of herbivorous insects as predicted by the latitude–niche breadth hypothesis and Rapoport's rule, respectively. We also aimed to study whether these species characteristics are positively linked with each other as stated by the niche breadth–range size hypothesis. Location: Europe (35–71° N). Time period: Present‐day. Major taxa: Geometrid moths (Lepidoptera: Geometridae). Methods: For every species, we compiled information on latitudinal distribution and host‐plant use based on available literature and online sources. We estimated the level of fundamental dietary specialization of each species while accounting for phylogenetic relationships among the host plants used. We also reconstructed a phylogeny including all studied moth taxa, in order to control for phylogenetic dependence in species characteristics. Phylogenetic least squares (PGLS) analyses were used to test each of our hypotheses. Results: We analysed 631 species of geometrids (85.2% of taxa within the biogeographical region) and found strong support for the latitude–niche breadth hypothesis and for Rapoport's rule. Fundamental dietary breadth was also found to be positively related to latitudinal range size, which supports the niche breadth–range size hypothesis. These results were retained when the subfamilies Ennominae and Larentiinae were analysed separately. Main conclusions: Our findings indicate that latitudinal clines in range size and fundamental dietary breadth covary in European geometrid moths and are likely to be drivers of increased species richness towards lower latitudes. This supports the idea that both characteristics should be studied simultaneously in order to unveil mechanisms structuring biodiversity patterns at the macroecological scale.